An immunotherapy effect analysis in Rasmussen encephalitis - Liba, Zuzana; Vaskova, Martina; Zamecnik, Josef; Kayserova, Jana; Nohejlova, Hana; Ebel, Matyas; Sanda, Jan; Ramos-Rivera, Gonzalo Alonso; Brozova, Klara; Liby, Petr; Tichy, Michal; Krsek, Pavel (BMC neurology, 2020)
BACKGROUND: Immune-mediated mechanisms substantially contribute to the Rasmussen encephalitis (RE) pathology, but for unknown reasons, immunotherapy is generally ineffective in patients who have already developed intractable epilepsy; overall laboratory data regarding the effect of immunotherapy on patients with RE are limited. We analyzed multiple samples from seven differently treated children with RE and evaluated the effects of immunotherapies on neuroinflammation. Immunotherapy was introduced to all patients at the time of intractable epilepsy and they all had to undergo hemispherothomy. METHODS: Immunohistochemistry, flow cytometry, Luminex multiplex bead and enzyme-linked immunosorbent assay techniques were combined to determine: 1) inflammatory changes and lymphocyte subpopulations in 45 brain tissues; 2) lymphocyte subpopulations and the levels of 12 chemokines/cytokines in 24 cerebrospinal fluid (CSF) samples and 30 blood samples; and 3) the dynamics of these parameters in four RE patients from whom multiple samples were collected. RESULTS: Sustained T cell-targeted therapy with cyclophosphamide, natalizumab, alemtuzumab, and intrathecal methotrexate (ITMTX), but not with azathioprine, substantially reduced inflammation in brain tissues. Despite the therapy, the distributions of CD8+ T cells and the levels of C-X-C motif ligand (CXCL) 10, CXCL13, and B cell activating factor (BAFF) in patients' CSF remained increased compared to controls. A therapeutic approach combining alemtuzumab and ITMTX was the most effective in producing simultaneous reductions in histopathological inflammatory findings and in the numbers of activated CD8+ T cells in the brain tissue, as well as in the overall CD8+ T cell population and chemokine/cytokine production in the CSF. CONCLUSIONS: We provide evidence that various T cell-targeted immunotherapies reduced inflammation in the brains of RE patients. The observation that intractable epilepsy persisted in all of the patients suggests a relative independence of seizure activity on the presence of T cells in the brain later in the disease course. Thus, new therapeutic targets must be identified. CXCL10, CXCL13 and BAFF levels were substantially increased in CSF from all patients and their significance in RE pathology remains to be addressed.
Keywords: Enzyme-Linked Immunosorbent Assay; Encephalitis; zánět; Female; Cytokines; dítě; předškolní dítě; ženské pohlaví; cytokiny; Immunotherapy; lidé; CD8-Positive T-Lymphocytes; mozek; Inflammation; encefalitida; ELISA; Male; CD8-pozitivní T-lymfocyty; imunoterapie; Brain; Child, Preschool; Child; mužské pohlaví; Humans